POTENSI ISOLAT LOKAL Bacillus thuringiensis SEBAGAI PENGHASIL PROTEIN PROTOKSIN DAN ENZIM KITINASE - Maisya Zahra AlBanna (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2014)
Bacillus thuringiensis secreted chitinase and protoxin protein which is play an important role in their pathogenicity to insect pest. This research was aimed to determined the ability of B. thuringiensis Lot II and B. thuringiensis 47 to produce chitinase enzyme and protoxin protein. Both of an isolates showed the clear zone when grown in a medium containing chitin agar, which is means they have secreted exochitinase enzyme. Optimum production of chitinase from B. thuringiensis subsp. pakistani was obtained at 24th hour,  B.  thuringiensis Lot II  was optimum at 21th hour and  B. thuringiensis 47 was optimum at 21st hour. The highest production of protoxin protein from B. thuringiensis Lot II was obtained at 33rd hour, whereas B. thuringiensis 47 at 36th hour.